Numerical analysis of phase change material filled with metal foam inside a cylindrical capsule - Asker, Mustafa; Al-Rawi, Mohammad; Genceli, Hadi (WILEY, 2023)
This research study performs a numerical assessment of the inward solidification of phase change material (PCM) integrated with metal foam (MF) encapsulated in a horizontal cylindrical geometry. The cylinder is not at melting temperature at the beginning, and its outer surface is subjected to convection boundary conditions. The 1D phase change model is resolved by applying the temperature transforming technique using an in-house computer program written in C++. Four different MF materials, aluminum, copper, nickel, and stainless steel, with various porosities, are used to examine the thermal behavior of the storage system. It is found that the use of copper as a MF with higher effective thermal conductivity remarkably enhances the elapsed time for complete solidification. Additionally, for a porosity value of 0.92, the time for total solidification of copper is diminished by 94%, while the complete solidification time for Stainless Steel is decreased by 65% in comparison to the situation where no MF is used.
Keywords: finite volume; metal foam; PCM; porosity; solidification; TES; LIQUID; Energy & Fuels